Evaluation Model of the SI-SKP Based on System Quality and User Acceptance: Integrating the DeLone & McLean Model with the Technology Acceptance Model (TAM) - Pratama, Aries Dian; Setiawan, Eman (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study evaluates the performance of the Employee Performance Target Information System (SI-SKP) at the Human Resources and Personnel Agency (BKPSDM) of the Surabaya City Government by integrating the DeLone & McLean Information Systems Success Model with the Technology Acceptance Model (TAM). The main objective is to analyze how the system and information quality of SI-SKP influence perceived ease of use and perceived usefulness, as well as their impact on user satisfaction, system usage, individual benefits, and organizational impact, considering that previous evaluations often overlooked the user perspective. The findings reveal that System Quality positively affects Perceived Usefulness, while Information Quality positively affects Perceived Ease of Use, both of which significantly influence User Satisfaction. Interestingly, however, Perceived Usefulness does not affect User Satisfaction, and User Satisfaction does not significantly influence Net Benefits (organizational impact). These results, together with the low R-square values, indicate the importance of non-technical factors such as organizational support and work culture in the successful implementation of SI-SKP. This study provides a comprehensive understanding of SI-SKP from both technical and user perspectives and offers practical suggestions for improvement as well as recommendations for further research.